Anatomical Assessment of the Temporopolar Artery for Revascularization of Deep Recipients. Issue 3 (30th May 2018) - Tayebi Meybodi, Ali; Benet, Arnau; Griswold, Dylan; Dones, Flavia; Preul, Mark C; Lawton, Michael T
Abstract: BACKGROUND: Intracranial–intracranial and extracranial–intracranial bypass options for revascularization of deep cerebral recipients are limited and technically demanding. OBJECTIVE: To assess the anatomical feasibility of using the temporopolar artery (TPA) for revascularization of the anterior cerebral artery (ACA), posterior cerebral artery (PCA), and superior cerebellar arteries (SCA). METHODS: Orbitozygomatic craniotomy was performed bilaterally on 8 cadaveric heads. The cisternal segment of the TPA was dissected. The TPA was cut at M3 -M4 junction with its proximal and distal calibers and the length of the cisternal segment measured. Feasibility of the TPA-A1 -ACA, TPA-A2 -ACA, TPA-SCA, and TPA-PCA bypasses were assessed. RESULTS: A total of 17 TPAs were identified in 16 specimens. The average distal TPA caliber was 1.0 ± 0.2 mm, and the average cisternal length was 37.5 ± 9.4 mm. TPA caliber was ≥ 1.0 mm in 12 specimens (70%). The TPA-A1 -ACA bypass was feasible in all specimens, whereas the TPA reached the A2 -ACA, SCA, and PCA in 94% of specimens (16/17). At the point of anastomosis, the average recipient caliber was 2.5 ± 0.5 mm for A1 -ACA, and 2.3 ± 0.7 mm for A2 -ACA. The calibers of the SCA and PCA at the anastomosis points were 2.0 ± 0.6 mm, and 2.7 ± 0.8 mm, respectively. CONCLUSION: The TPA-ACA, TPA-PCA, and TPA-SCA bypasses are anatomically feasible and may be used when the distal caliber of the TPA stump is optimal to provide adequate blood flow. This study lays foundations for clinical use of the TPA for ACA revascularization in well-selected cases.